Blood pressure during pregnancy is a useful predictive maker for hypertension and dyslipidemia later in life, a population-based, cross-sectional study. (May 2016) - Iino, Kaori; Higuchi, Tsuyoshi; Ogawa, Mariko; Yamauchi, Yoko; Misaki, Naoko; Tanaka, Kanji; Takahashi, Ippei; Mizunuma, Hideki
Highlights: In this study, blood pressure levels during pregnancy were assessed as predictive makers of future hypertension and dyslipidemia in later adulthood. Blood pressure levels during pregnancy may be predictive of future risk factors for CVD. Our results showed that a 10 mmHg increase in the mean diastolic blood pressure level between gestational weeks 12 and 42 conferred a 1.70- and 1.55-fold increase in the risk of hypertension and dyslipidemia, respectively, in later life. Abstract: Objective: Pregnancy is an opportunity for women to become aware of their risk of cardiovascular disease (CVD), because physiologic responses to dynamic hemodynamic changes can be observed during pregnancy. Accordingly, we hypothesized that blood pressure levels during pregnancy may be associated with the risk of CVD later in life. Study design: We used data from the Iwaki Health Promotion Project and designed a population-based, cross-sectional study. In this study, Maternity Health Record Books were collected from women over 40 years of age in order to obtain reliable data regarding past pregnancies. Of a total of 642 women, 432 were selected according to the study criteria. Main outcome measures: The associations between blood pressure levels during pregnancy and major CVD risk factors (hypertension and dyslipidemia) were analyzed retrospectively. Results: A 10 mmHg increase in the mean diastolic blood pressure level between gestational weeks 12 and 42 conferred a 1.70- and 1.55-fold increase in the risk of hypertension and dyslipidemia, respectively, in later life. Conclusions: Blood pressure levels during pregnancy may be associated with CVD risk and could therefore be a useful predictive marker.